When the rich meet the poor: Interactions with the homeless in New York City - Kevin C. Corinth; Grace Finley (American Enterprise Institute (AEI), 2017)
As inequality rises in the United States, the rich and poor are increasingly unlikely to interact with one another. Corinth and Finley use data on "311" calls reporting homeless individuals in New York City between 2010 and 2016 to determine whether the rich are more likely to see or interact with the unsheltered homeless population. They also examine the response by police to encampment calls and by social service workers to assistance calls.
Keywords: A; 330; homelessness; New York City (NYC)